215 Preterm birth in relation to occupational lifting assessed by a Job Exposure Matrix: findings from the Danish National Birth Cohort. (11th October 2013) - Svendsen, S W; Frost,; Mocevic,; Jørgensen,; Andersen, Nybo; Bonde,
Abstract : Objective: The question remains unresolved if the risk of preterm birth increases with increasing occupational lifting. Previous studies have generally used individual-based exposure assessment relying on self-report, and based on this approach, we have observed an exposure-response relation between total load lifted per day and preterm birth. 1 To corroborate our finding, we aimed to examine the risk of preterm birth among primigravidas in relation to occupational lifting during pregnancy using group-based exposure assessment. Methods: Within the Danish National Birth Cohort (DNBC), we identified 24, 833 occupationally active primigravidas with singleton pregnancies, who as a minimum entered gestational week 23 and provided interview data while pregnant. We constructed a Job Exposure Matrix (JEM) based on information from all women in the DNBC, who were pregnant when interviewed. The JEM cross-tabulated job and industry information with average total loads lifted per day. Each woman received an exposure estimate from the JEM. We used Cox regression analysis adjusting for age, smoking, BMI, and alcohol consumption. The women were followed from start of week 23 or interview date, whichever came last, until end of week 37 or pregnancy termination, whichever came first. Results: A total of 1601 preterm births occurred. Adjusted HRs increased with increasing occupational lifting, reaching a HR of 1.42 (95% CI 1.13–1.77) for women in the highest exposure category (>200 kg per day), when compared to non-lifters. Conclusion: We used group-based exposure assessment to minimise information bias and attenuation of exposure-response relations. Among women in jobs categorised with a lifting exposure of >200 kg per day, we found support for a moderately increased risk of preterm birth. Reference: 1 Runge SB, Pedersen JK, Svendsen SW, Juhl M, Bonde JP, Nybo Andersen AM. Occupational lifting and preterm birth: a study within the Danish National Birth Cohort. EPICOH 2011 (abstract).